Pengaruh Pembelajaran Seni Budaya dan Prakarya (SBDP) Terhdap Pengembangan Kreativitas Siswa Kelas V di SDN Darmaga IV - Siti Hulfah; Zaenal Ibrohim (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
The development of technology and information has a great influence on humans. Awareness of the importance of developing student creativity, especially in the subject of Arts, Culture and Crafts (SBdP) is still lacking. So, it can have an influence on the development of student creativity. This study aims to determine the reality of learning Arts, Culture and Crafts (SBdP) at SDN Darmaga IV. This study was conducted at SDN Darmaga IV, the influence of arts and culture learning on student creativity, the influence of crafts on student creativity and the influence of learning arts, culture and crafts (SBdP) on the development of creativity of class V students at SDN Darmaga IV with the type of research used is quantitative descriptive, namely to determine the influence between 3 variables. The number of samples used was 20 students in class V SDN Darmaga IV. The data collection techniques used were questionnaires and observations. While the data analysis techniques processed and analyzed using IMB Statistic SPSS 22. The reality of learning Arts, Culture and Crafts (SBdP) for grade V at SDN Darmaga IV is in the moderate category. This is shown based on the results of observations from four aspects of indicators, namely multilingual, multidimensional, multicultural, and multi-intelligence. X1 against Y obtained a t-count value > from t-table 2, 032 > 1.729 there is an influence of learning arts, culture and crafts on student creativity. X2 against Y t-count value > t-table 2, 638 > 1.729 there is an influence of crafts on student creativity. And X1, X2 against Y f-count value > f-table 3, 49 > 23, 806 there is an influence of arts, culture and crafts (SBdP) on the development of creativity of grade V students at SDN Darmaga IV. This means that the results of this study indicate that there is an influence of SBdP learning on the creativity of grade V students at SDN Darmaga IV.